2013
DOI: 10.1039/c3ob40615f
|View full text |Cite
|
Sign up to set email alerts
|

Expeditious synthesis of bacterial, rare sugar building blocks to access the prokaryotic glycome

Abstract: Bacteria have unusual glycans which are not accessible by isolation. Herein, we describe a general and divergent strategy for the synthesis of the rare, bacterial deoxy amino hexopyranoside building blocks from d-mannose. The methodology is applied to the first total synthesis of the l-serine linked trisaccharide of Neisseria meningitidis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
51
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 31 publications
0
51
0
Order By: Relevance
“…established that GlcNAz is metabolically processed into H. pylori ’s glycoproteins. 64 Further, Memmel et al . found that GlcNAz is incorporated into S. aureus ’ surface glycans.…”
Section: Figmentioning
confidence: 99%
“…established that GlcNAz is metabolically processed into H. pylori ’s glycoproteins. 64 Further, Memmel et al . found that GlcNAz is incorporated into S. aureus ’ surface glycans.…”
Section: Figmentioning
confidence: 99%
“…10 This sulfated tetrasaccharide is of signicant biological interest due to its unique expression at the site of chronic inammation. 15 In continuation of our studies directed towards the synthesis of glycosamine containing glycoconjugates, [16][17][18] we report herein a convenient synthesis of orthogonally protected Tn antigen and its application in the total synthesis of MECA-79 antigen. 11,12 Soon aer its isolation, Bélot and co-workers reported a synthesis of the n-octyl derivative of MECA-79.…”
Section: Introductionmentioning
confidence: 97%
“…In addition, synthetic approaches from naturally-abundant carbohydrates often require lengthy synthetic routes which make rare sugars very expensive 3. An alternative and potentially more versatile approach is the de novo asymmetric synthesis of deoxy sugars 4,5.…”
Section: Introductionmentioning
confidence: 99%